Pengaruh Bentuk dan Ketinggian Perangkap Sticky Trap Kuning Terhadap Lalat Buah (Bactrocera spp.) (Diptera:Tephritidae) Pada TanamanTomat (Solanum lypersicum mill.) di Dataran Rendah - Chornelius Karo-Karo; Yuswani Pangestiningsih; Lisnawita Lisnawita (Universitas Sumatera Utara, 2015)
The aim of this research was to get the best shape and elevation of yellow sticky trap to controlfruit fly. Research was conducted from September 2013 until November 2013 at Kuta Tualahvillage, Kecamatan Kutalimbaru, Kabupaten Deli Serdang, North Sumatera on 57 meter above sealevel. The research was conducted using Randomized Block Design (RAK) factorial with twofactors and 5 replications. The first factor was U1= 100 cm, U2= 150 and U3= 200 cm and thesecond factor was T1= circle, T2= square, T3= sylinde. The results showed that circle yellowsticky trap with 150 cm elevation more effective for trapping male and female fruit fly than theothers. The highest number of larvae in tomatoes fruit was founded at square yellow sticky trapwith 100 cm elevations. Highest tomatoes production (21.86 ton / ha) was founded at circle yellowsticky trap with 150 cm elevation, meanwhile the lowest (3.70 ton / ha) was founded at squareyellow sticky trap with 100 cm elevation.Key words: Bactrocera spp., fruit fly, tomato, trap